Diverse intracellular pathogens activate type III interferon expression from peroxisomes - Odendall, Charlotte; Boulant, Steeve (Nature immunology, 2014)
Type I interferon responses are considered the primary means by which viral infections are controlled in mammals. Despite this view, several pathogens activate antiviral responses in the absence of type I interferons. The mechanisms controlling type I interferon–independent responses are undefined. We found that RIG-I like receptors (RLRs) induce type III interferon expression in a variety of human cell types, and identified factors that differentially regulate expression of type I and type III interferons. We identified peroxisomes as a primary site of initiation of type III interferon expression, and revealed that the process of intestinal epithelial cell differentiation upregulates peroxisome biogenesis and promotes robust type III interferon responses in human cells. These findings highlight the importance of different intracellular organelles in specific innate immune responses.